Molecular confirmation of nine cases of Cornelia de Lange syndrome diagnosed prenatally. (9th December 2013) - Dempsey, M. A.; Knight Johnson, A. E.; Swope, B. S.; Moldenhauer, J. S.; Sroka, H.; Chong, K.; Chitayat, D.; Briere, L.; Lyon, H.; Palmer, N.; Gopalani, S.; Siebert, J. R.; et al.
ABSTRACT Objectives Cornelia de Lange syndrome (CdLS) is characterized by distinct facial features, growth retardation, upper limb reduction defects, hirsutism, and intellectual disability. NIPBL mutations have been identified in approximately 60% of patients with CdLS diagnosed postnatally. Prenatal ultrasound findings include upper limb reduction defects, intrauterine growth restriction, and micrognathia. CdLS has also been associated with decreased PAPP‐A and increased nuchal translucency (NT). We reviewed NIPBL sequence analysis results for 12 prenatal samples in our laboratory to determine the frequency of mutations in our cohort. Methods This retrospective study analyzed data from all 12 prenatal cases with suspected CdLS, which were received by The University of Chicago Genetic Services Laboratories. Diagnostic NIPBL sequencing was performed for all samples. Clinical information was collected from referring physicians. Results NIPBL mutations were identified in 9 out of the 12 cases prenatally (75%). Amongst the NIPBL mutation‐positive cases with clinical information available, the most common findings were upper limb malformations and micrognathia. Five patients had NT measurements in the first trimester, of which four were noted to be increased. Conclusion We demonstrate that prenatally‐detected phenotypes of CdLS, particularly severe micrognathia and bilateral upper limb defects, are associated with an increased frequency of NIPBL mutations. © 2013 John Wiley & Sons, Ltd.